Inferiority feeling pada remaja panti asuhan: Bagaimana peranan konsep diri dan dukungan sosial? - Noviekayati, IGAA; Farid, Muhammad; Amana, Lidya Nur (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractInferiority feeling in adolescents who live in orphanages needs attention because if left unchecked it can cause adolescents to lose their potential. This study intends to examine the role of self-concept and social support on inferiority feelings. Participants in this study were 71 teenagers who were taken purposively from seven orphanages in Surabaya. The research data were taken using the inferiority feeling scale (?=0.874), the self-concept scale (?=0.935), and the social support scale (?=0.938) which were compiled by the researcher himself. The results of data analysis using multiple regression analysis show that self-concept and social support simultaneously have a negative effect on inferiority feeling. Partially both variables also have a significant negative effect on inferiority feeling. The implication of this research is as a basis of reference for caregivers, counsellors or the community in paying attention to the psychological needs of orphaned youth.Keywords: Inferiority Feeling; Self-concept; Social support AbstrakInferiority feeling pada remaja yang tinggal di panti asuhan perlu mendapatkan perhatian sebab jika dibiarkan dapat menyebabkan remaja kehilangan potensi dirinya. Penelitian ini bermaksud untuk menguji peranan konsep diri dan dukungan sosial terhadap inferiority feeling. Partisipan dalam penelitian ini sebanyak 71 remaja diambil dengan teknik purposive sampling dari tujuh panti asuhan di Surabaya. Data penelitian diambil menggunakan skala inferiority feeling (?=0,874), skala konsep diri (?=0,935), dan skala dukungan sosial (?=0,938) yang disusun sendiri oleh peneliti. Hasil analisis data menggunakan regresi ganda menunjukkan secara simultan konsep diri dan dukungan sosial memiliki pengaruh negatif terhadap inferiority feeling. Secara parsial kedua variabel juga memiliki pengaruh negatif yang signifikan terhadap inferiority feeling. Implikasi penelitian ini adalah sebagai dasar acuan kepada pengasuh, konselor ataupun masyarakat dalam memperhatikan kebutuhan psikologis remaja panti asuhan.Kata kunci: Dukungan sosial; Inferiority feeling; Konsep diri